Investors valuation for assets liquidity and safety and the corporate-treasury yield spread - Niestroj, Benjamin (Technische Universität Dortmund, 2012)
The present study seeks to explain the non-default component of corporate- U.S. Treasury yield spreads. This is done by assuming, along the lines of Krishnamurthy and Vissing-Jorgensen (2012), that investors' valuation for asset-specific liquidity and safety features is being priced. For that purpose I modify a standard asset pricing model by allowing certain groups of assets to directly contribute to utility. Empirical tests of the model's implications con firm that view and show that changes in the supply of more liquid and safe assets cause a stronger impact on corporate-Treasury yield spreads compared to changes in the supply of less liquid and safe assets. Finding this systematic pattern, points to the existence of a demand function for liquidity and safety attributes. Further I provide evidence that liquidity and safety are priced separately from commonly used controls for economic risk and default risk factors as well as liquidity risk controls.
Discussion Paper / SFB 823;53/2012
Keywords: Asset Pricing; Corporate-Treasury Bond Yield Spread; Credit Risk; Liquidity and Safety adjusted CAPM; Liquidity Premium; 310; 330; 620